United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper examines from an empirical standpoint the impact of fiscal aggregates on the evolution of output and the real effective exchange rate in the United Kingdom from the late 1970s to the present. It finds that the size of the dynamic fiscal multipliers is small, and often statistically nonsignificant. The paper also finds that the direction of the impact of taxes and government consumption, but not of social transfers, is, if anything, the reverse of that predicted by standard Keynesian models.